The influence of extreme thermal stress on the physiological and psychological characteristics of young women who sporadically use the sauna: practical implications for the safe use of the sauna - Podstawski, Robert; Borysławski, Krzysztof; Józefacka, Natalia Maja; Snarska, Jadwiga; Hinca, Bożena; Biernat, Elżbieta; Podstawska, Anna (Frontiers in Public Health, 2024)
Background: Despite extensive research into sauna use, the impact of extreme thermal stress on the physiological and psychological characteristics of sauna users has not been examined to date. Aim: The aim of this study was to determine the effect of 20-minute sauna sessions (80°C and 120°C) on the physiological and psychological characteristics of women who sporadically visit the sauna. Methods: The study was conducted on 22 full-time female university students. Physical activity (PA) levels were evaluated with the Polish short version of the International Physical Activity Questionnaire (IPAQ). Anthropometric characteristics were measured before the first sauna session with the InBody270 body composition analyzer. Physiological parameters, including heart rate (HR), energy expenditure, physical effort, and systolic (SBP) and diastolic blood pressure (DBP), were assessed indirectly using Polar V800 HR monitors and the Omron M6 Comfort blood pressure monitor. The participants' well-being was assessed with the Profile of Mood States (POMS) questionnaire. The presence of significant correlations between heat exhaustion/heat stress variables and syncope during the second sauna session was examined using classification and regression trees (CRT) and the cross-validation technique. Results: Twenty-minute sauna sessions (80°C and 120°C) induced a significant (p<0.001) decrease in the values of SBP (excluding the temperature of 120°C), DBP, and body mass, and a significant increase in HR and forehead temperature. Exposure to a temperature of 80°C led to a significant (p<0.001) increase in vigor with a simultaneous decrease in tension, depression, anger, fatigue, and confusion. In turn, sauna bathing at a temperature of 120°C had the opposite effect on the above mood parameters. Vomiting and confusion were the main predictors of syncope that occurred in some of the surveyed women. Conclusions: Excessive air temperature can induce symptoms characteristic of heat exhaustion and heat stress, i.e., nausea, heavy sweating, fast weak, or strong HR, high body temperature, and confusion. Therefore, sauna bathing at a temperature of 80°C can be recommended to women who sporadically use the sauna, whereas exposure to a temperature of 120°C is not advised in this group of sauna users.